An electrophysiological investigation of skeletal muscles in polymyositis - R. E. P. Sica; Olga P. Sanz; Nidia Aguilera; A. Colombi (Arquivos de Neuro-Psiquiatria)
An electrophysiological study has been made of the extensor digitorum brevis, thenar and hypothenar muscles in 25 patients with chronic and acute polymyositis. It was found a reduction of the number of functioning motor units in some patients with chronic polymyositis and only in one of those affected by acute polymyositis. The sizes of the surviving units suggested that the results could be explained in terms of a primary muscle involvement mainly in acute polymyositis, while in chronic polymyositis a combination of primary and neurogenic involvement of muscle fibers might take place.